Agronomic evaluation of Chamaecrista rotundifolia accessions under grazing in southern Ethiopia - Larbi, Asamoah; Thomas, D.; Ochang, J. (1993)
Forage production of 16 C. rotundifolia accessions was compared with that of Stylosanthes scabra cv Seca under grazing in a subhumid, medium altitude acid soil site at Soddo, southern Ethiopia. Large variations were observed in dry matter production, days to flower initiation, canopy height and crown spread. The productivity of accessions ILCA 14163, 10068, 14168 and 14162 was comparable to that of Seca. These four accessions are recommended for further evaluation.